Qui copier ? Les stratégies d’apprentissage social chez les animaux - Charlotte Canteloup (Revue de Primatologie)
The existence of culture in nonhuman animals has been a particularly hot debate, historically opposing anthropologists to biologists. According to the latter, the mind, society and culture of humans are rooted in cognitively simple mechanisms that we share with other animals. Understanding the behavioural and cognitive precursors of human culture requires experimental study of social learning and comparative phylogenetic analysis of living species to bring insight into the evolution of culture. The complexity of human culture has been proposed to be partly due to an efficient and accurate propagation of new knowledge. Copying the behavior exhibited by the majority of individuals or by the most prestigious, successful, represents different ‘who’ social learning strategies, also called rules. This paper reviews similar learning biases that have been found in different primate species, inviting us to consider that strategic learning behaviour is a shared trait, at least, with our primate cousins.